Online Buying and Selling Transactions of Online Stores in Sumedang from Fiqh Muamalah Perspective - Pazri, Deva Fariz; Arismunandar, Ihsan Nurfauzi; Hodijah, Ela (International Journal of Sharia Business Management, 2024)
Online transactions are order transactions in the global era business model via the internet between sellers and buyers. The focus of the problem studied in this article is to find out whether online buying and selling transactions in Sumedang shops are in accordance with fiqh muamalah or not. This study aims to explain the Review of Fiqh Muamalah on Online Buying and Selling Case Study of Online Shops in Sumedang. The method used in this study is a qualitative method. The results of the analysis of the review of fiqh muamalah on online buying and selling transactions refer to the principles of Islamic law that regulate economic transactions, including in the context of e-commerce.